Comparing Management Programs to Reduce Red–tailed Hawk Collisions with Aircraft. (19th May 2021) - Washburn, Brian E.; Pullins, Craig K.; Guerrant, Travis L.; Martinelli, Gregory J.; Beckerman, Scott F.
ABSTRACT: Wildlife‐aircraft collisions (wildlife strikes) pose a serious safety risk to aircraft. Raptors (i.e., hawks and owls) are one of the most frequently struck guilds of birds within North America. Although raptors (most notably red‐tailed hawks [ Buteo jamaicensis ]) are commonly managed at most airports and military bases, there is no scientific information available regarding comparisons of the efficacy of raptor management programs for reducing raptor‐aircraft collisions. Therefore, we conducted a study to examine the efficacy of 2 raptor hazard management programs implemented at Chicago's O'Hare International Airport (ORD). The first raptor management program (Phase I) occurred during January 2010–June 2013 and was characterized by intensive and sustained live‐trapping and translocation efforts. The second raptor management program (Phase II) occurred during July 2013–December 2016 and involved live‐trapping and translocation of specific age classes and increased lethal removal of problematic individual hawks. Compared with Phase I, there were 47% fewer red‐tailed hawk strikes (52 in Phase I and 28 in Phase II) and 67% fewer damaging red‐tailed hawk strikes (6 in Phase I and 2 in Phase II) during Phase II of the management programs. Our findings demonstrate that airport wildlife management decisions based on scientific data and biological information can aid in reducing wildlife strikes, financial losses, and ultimately airport liability while increasing human safety. The decision matrix regarding the components of an airport raptor hazard management program involves a variety of biological, geographic, logistical, economic, and socio‐political variables. Our study provides a scientific foundation for informing such management decisions. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. : We compared 2 raptor management programs to determine their efficacy in reducing red‐tailed hawk‐aircraft collisions. The fewest red‐tailed hawk‐aircraft collisions occurred during the raptor management program developed from actual field research.